High‐resolution pluronic‐filled microchip CE‐SSCP analysis system via channel width control. Issue 4 (30th November 2015) - Shin, Giyoung; Kim, Dong‐Kyun; Doh, Junsang; Lee, Daeyeon; Lee, Nam Ki; Jung, Gyoo Yeol
Abstract : Although the resolution of CE‐SSCP has been significantly improved by using a poly(ethyleneoxide)‐poly(propyleneoxide)‐poly(ethyleneoxide) (PEO‐PPO‐PEO; Pluronic ® ) triblock copolymer as a separation medium, CE‐SSCP on a microchip format is not widely applicable because their resolution is limited by short channel length. Therefore, a strategy to improve the resolution in channels of limited lengths is highly required for enabling microchip‐based CE‐SSCP. In this study, we developed a high‐resolution CE‐SSCP microchip system by controlling the width of the pluronic‐filled channel. We tested four different channel widths of 180, 240, 300, and 400 μm, and found that 300 μm showed the highest resolution in the separation of two pathogen specific markers. Potential applications of our method in various genetic analyses were also shown by using SNP markers for spinal muscular atrophy.